The Form Of Decision Acceptance Of The Muzakarah Of National Council Of Fatwa Committee By The Syarie Legal Adjudication Committee Of The State Of Pahang - Miziazam, Yahya; Mansor, Sulaiman; Irwan, Mohd Subri; Muhd Nasiruddin, Asman (Usuli Faqih Research Centre PLT, 2018)
The role of the National Council of Fatwa Committee (Jawatankuasa Fatwa Majlis Kebangsaan) as a national body that issues fatwa is authorized and acknowledged. However, the fatwa issued by this body still needs to go through the State Fatwa Committee before it is adopted at the state level. Hence, this article aims to analyze the decision acceptance forms of theMuzakarah of the National Council of Fatwa Committee (MJF) by the Pahang Syarie Legal Adjudication Committee (JPHSNP) for the fatwa that has been discussed and decided on the national level. Based on the method of data collection and analysis of document contents, this literature study has revisited previous studies conducted on the issue of fatwa coordination in Malaysia. However, after the study, the findings have yet to achieve the goals that are fully desired. The findings conclude that, there are three forms of decision adopted by JPHSNP against the fatwa decided by MJF i.e agreeing unanimously, agreed by majority or deferring decisions.